2017
DOI: 10.1293/tox.2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium exposure on medaka (<i>Oryzias latipes</i>) testes

Abstract: Adult male medaka (Oryzias latipes) were exposed to 10 ppm of cadmium for 96 h, and the testes were examined histopathologically. Numerous apoptotic cells were found in the spermatogonia and spermatocytes at 72 and 96 h after initiation of cadmium exposure, and the pyknotic index, TUNEL-positive rate, and cleaved caspase-3-positive rate in the spermatogonia and spermatocytes of the cadmium-treated group were higher compared with the control group. No significant difference between the control and cadmium-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
2
4
0
Order By: Relevance
“…The results of the present study revealed that a 50 mg/kg exposure to cadmium induces significant apoptosis of spermatogonia and spermatocytes in the testes of adult Iberian ribbed newts, indicating that germ cells in these differentiation stages are highly sensitive to cadmium. The histopathologic findings of the present study are similar to those reported for cadmium-exposed frogs, such as B. melanostictus and R. hexadactyla Lesson , and fish, such as O. latipes 24 , 25 , 26 . To our knowledge, this is the first report of the histomorphologic characteristics of cadmium-induced testicular dysfunction in newts.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The results of the present study revealed that a 50 mg/kg exposure to cadmium induces significant apoptosis of spermatogonia and spermatocytes in the testes of adult Iberian ribbed newts, indicating that germ cells in these differentiation stages are highly sensitive to cadmium. The histopathologic findings of the present study are similar to those reported for cadmium-exposed frogs, such as B. melanostictus and R. hexadactyla Lesson , and fish, such as O. latipes 24 , 25 , 26 . To our knowledge, this is the first report of the histomorphologic characteristics of cadmium-induced testicular dysfunction in newts.…”
supporting
confidence: 88%
“…injection of 50 mg/kg of cadmium induced apoptosis of the spermatogonia and spermatocytes in Iberian ribbed newts. The observed histopathologic findings in the testes of newts exposed to cadmium were similar to those reported for testes of several frogs, such as Bufo melanostictus and Rana hexadactyla Lesson 24 , 25 , and fish, such as Oryzias latipes 26 .…”
supporting
confidence: 84%
“…Cadmium-induced testis showed increased activity of caspase 3 and 9, which increases the number of morphological signs of apoptosis, including chromatin decondensation and marginalization in primary spermatocytes, loss of the nuclear envelope in the spermatogonium, disruption of mitochondrial membrane potential (MMP), degradation of cytoplasmic organelles, and DNA distribution [ 102 ]. The testicles of rats [ 103 ], fish [ 104 ], and lizard [ 105 ] all showed evidence of cadmium-induced spermatogonia and spermatocyte apoptosis. The concentration-dependent effect of cadmium on human embryonic germ cell apoptosis was revealed by immune signaling detection of caspase 3 in testicular tissue [ 106 ].…”
Section: Effect Of Cadmium On Spermatogenesismentioning
confidence: 99%
“…Various morphological characteristics of apoptosis, eg, chromatin condensation and marginalization in primary spermatocytes, degeneration of cytoplasmic organelles, disappeared nuclear envelope in spermatogonium, and fragmentation of DNA were observed in Cd‐intoxicated testes of freshwater crab ( Sinopotamon henanense ), along with increased activities of caspase‐3 and ‐9 in a concentration‐dependent manner (Wang et al, 2011). Other morphological and ultrastructural studies have also reported Cd‐induced apoptosis of spermatogonia and spermatocytes in rodents (Boujelben, Abdennabi, Guermazi, & Elfeki, 2018; Niknafs et al, 2015), fish (Hirako, Takeoka, Furukawa, & Sugiyama, 2017) and newt (Hirako et al, 2017) testis, respectively. A concentration‐dependent effect of Cd on apoptosis of human fetal germ cells was illustrated by immunohistochemical detection of caspase‐3 in testicular tissue under in vitro conditions (Angenard et al, 2010).…”
Section: Cadmium‐mediated Toxicity In Testesmentioning
confidence: 90%